The impact of air pollution on the incidence and mortality of COVID-19 - Abhinav Karan; Kabeer Ali; Surujpal Teelucksingh; Sateesh Sakhamuri (BMC, 2020)
Abstract Air pollution is the most significant environmental risk factor for all-cause mortality, and it has caused substantial disability-adjusted life-years and economic loss. Air pollution intensified the mortality during past pandemics, Spanish flu in 1918 and SARS-CoV-1 in 2003. It increases host susceptibility and virulence of respiratory infections and reduces viral clearance. Thus, a question arises whether there will be any impact of air pollution on the current pandemic coronavirus disease 2019 (COVID-19)? Thus far, history and science are directing towards an immense potential impact of air pollution on the COVID-19 pandemic. Some of the devastated countries with the current pandemic are those with a poor air quality index. Further epidemiological and ecological studies are necessary to confirm this association. Also, countries must mobilize funding for mitigation of air pollution to benefit environmental health and ameliorate its potential effects on pandemics of the future.